Mechanically robust and electrically conductive graphene-paper/glass-fibers/epoxy composites for stimuli-responsive sensors and Joule heating deicers. (November 2017) - Zhang, Qiangqiang; Yu, Yikang; Yang, Kaichun; Zhang, Baoqiang; Zhao, Keren; Xiong, Guoping; Zhang, Xingyi
Abstract: In this article, by composing three functional constituents into a multilayered structure with well-bonded interfaces, a conductive graphene-papers (GPs)/glass-fibers (GFs) reinforced epoxy composite (GPs-GE) with outstanding mechanical robustness, high electrical conductivity and sensitive stimuli-responsive performance is highlighted. Thereinto, GPs serves as a stimuli-responsive and Joule heating chip due to its superiorities on both of mechanical and electrical properties, while GFs possessing mechanically protective and strengthening functionality. The stimuli-responsive characterizations by electrical resistance change reveal the synchronous sensing properties of GPs-GE to different stimuli inputs such as mechanical deformation, temperature fluctuation and humidity. Subsequently, Joule heating and de-icing/anti-icing properties of GPs-GE are investigated symmetrically, indicating its large heating rate, high efficiency of energy conversion and low cost. Such superior performance of GPs-GE confirms that the design of multilayer microstructure to achieve multi-functionalization paves a novel way to scale-up fabrication of advanced graphene composites, indicating promising applications as mechanically reinforcing elements, stimuli-responsive sensors and electrical Joule heating chips in intelligent engineering monitoring and icing-induced disaster prevention at low-temperature environment. Graphical abstract: